Influence of the surface state on the dynamics of the bulk density of O2 molecules in mixtures with inert and molecular particles in gas and glow discharge - Ochkin, V. N.; Lagunov, V. V.; Bernatskiy, A. V. (Applied physics. B, Lasers and optics, 2022)
The dynamics of the bulk density of O 2 molecules in a gas-discharge tube was studied by diode laser spectroscopy in mixtures of oxygen with He, Ne, Ar, Xe atoms, H 2 O and CH 4 molecules. The measurements were carried out both in the process of gas inflow into the tube and after the glow discharge was switched on with different methods of preliminary processing of its surface in a vacuum and a discharge in an O 2 –He mixture. The influence of the surface preparation method on the behavior of the O 2 concentration both in a neutral gas and in the discharge plasma was revealed. This influence was associated with the participation of both the initial particles and the decomposition products of molecules in heterogeneous adsorption/desorption processes.